Cracks in the Foundation: How Relational Communication Dynamics Predict Performance Improvement in Cross-Functional Teams - Vera~M. Schweitzer; Fabiola~H. Gerpott; Nale Lehmann-Willenbrock; Sander de Leeuw; Michaéla Schippers; Jiachun Lu (Journal of Supply Chain Management, 2025)
Cross-functional teams are vital decision-making units in supply chain management, and scholars emphasize the need to understand how team processes shape performance improvement. Despite promising research on communication within cross-functional teams, scant attention has been paid to real-time communication patterns—integral to behavioral supply chain management—which are fundamental to team processes in practice. This article posits, drawing on interaction ritual theory, that early communication patterns are correlated with the performance trajectories of cross-functional teams, suggesting a potential influence. The authors tested this idea in a complex supply chain management simulation featuring cross-functional teams. They employed a novel coding approach to capture temporal interactions, which yielded 25,641 coded verbal behaviors from cross-functional team meeting interactions. To identify systematic communication patterns, lag sequential analysis was performed on this corpus of data. The results show that the frequency of relational communication was associated with weaker performance improvement in cross-functional teams across six simulation iterations. Even more interestingly, when relational communication was frequently followed by task-oriented communication, no association with team performance improvement was observed. Further, cross-functional teams in which relational communication was more frequently followed by counterproductive communication showed notably weaker performance improvements. Focusing on interactional flow within team dynamics, this research challenges the common belief regarding the value of broadly evaluating cross-functional teams. As such, it advocates for adopting both a behavioral and a temporal lens to uncover how cross-functional teams can prevent detrimental interactions in their daily operations.
Keywords: 330; behavioral supply chain management; communication pattern; cross-functional teams; interaction coding; lag sequential analysis; latent growth modeling